IMPLEMENTASI ILMU EKONOMI DALAM PENGEMBANGAN KOTORAN SAPIMENJADI BARANG BERNILAI EKONOMIS TINGG - Mimi Cahyani; Sahar Sahar (Pinus Publishing, 2025)
The livestock industry is one of the agricultural sub-sectors that produces food products in the form of animalfoods such as eggs, meat, and milk. The development of this livestock industry is influenced by the demand forthese animal sources. Other results of cattle farming in the form of waste cause unpleasant odors, odors in theenvironment, disrupt beauty and can cause various diseases. In small livestock businesses, this problem maynot be so noticeable. A small amount of waste can be handled. Unlike large-scale livestock businesses. Thewaste produced will be very large. If its management is not carried out properly, it will have badconsequences. The stench from cow dung reduces the comfort and quality of life of the community around thepen or farm. The accumulation of dung can also trigger protests from the surrounding community and reducethe aesthetic value of the environment. Cow dung that is left to pile up in damp places can be a growingmedium for psilocybin mushrooms, which can be abused as narcotics and cause hallucinations and mentaldisorders. The purpose of this study is to change cow dung waste into something that has economic value andhas a positive impact on farmers and the surrounding community. The research used is descriptive qualitative,the data collection techniques used are observation, interviews and documentation. Data analysis is obtainedby collecting data, reducing data, presenting data and then drawing conclusions. This study shows that cowdung waste can be converted into something of high economic value, this can be done by utilizing cow dungwaste as organic fertilizer, biogas, eco-enzyme and bioarang (cow dung charcoal briquettes). The utilizationof cow dung waste also has a significant impact on changes in the economy of the community using biogasand organic fertilizer. In addition, the impact of environmental pollution can also be reduced. Cattle farmersstill have very little information about the utilization of cow dung waste into materials of economic value,therefore support from the government from the modeling sector is also very much needed. Not only that,academics, researchers and environmental activists also need to provide understanding through training andcounseling regarding the utilization of cow dung waste into materials of high economic value